Ідентифікація знань в електронних бібліотеках - Kanishcheva, O. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2009)
The method of comparator identification is considered as one the logical methods of Data Mining. It is used to solve problems of processing natural language texts in automatized information library systems.